If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -3) = 7x Reorder the terms: 8(-3 + x) = 7x (-3 * 8 + x * 8) = 7x (-24 + 8x) = 7x Solving -24 + 8x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -24 + 8x + -7x = 7x + -7x Combine like terms: 8x + -7x = 1x -24 + 1x = 7x + -7x Combine like terms: 7x + -7x = 0 -24 + 1x = 0 Add '24' to each side of the equation. -24 + 24 + 1x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 1x = 0 + 24 1x = 0 + 24 Combine like terms: 0 + 24 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| x+4y=21 | | 4(x+10)+10=9x | | 5(x-3)+3x=12x | | 6(x-10)=2x | | 10(x-8)(5x+1)=0 | | (x-7)(5x+2)=0 | | (x-9)(x+3)=0 | | 4x(x+2)=0 | | 4(x+9)=16x-10x | | 7(x+4)+4x=16x | | 10(x+4)=14x | | 3(8-x)=3x | | 2(x+12)=9x | | 5(x+3)=7x | | 5(x+3)=3x | | 5(x+20)=25x | | 50x+100=25x | | 10x=12x+36 | | 20x=150-10x | | 24-3x=5x | | 7x=5x+22 | | 2(x+35)=16x | | 20x+70=18x | | 20x+50=15x | | 8x=6x+80 | | 10+4x=-26+6x | | 4x+10=6x-26 | | xa-c=b | | 5-.5(x-6)=4 | | 8m+7=5m+16+3m | | .5(6-z)=z | | 1-s=6-6s |